Correspondence between A.V. Amfiteatrov and V.Ya. Bryusov (1909‒1912) - Alexander S. Alexandrov (Литературный факт)
For the first time, the article presents in full the correspondence between Valery Bryusov and the journalist and prose writer, popular feuilletonist, and author of historical novels Alexander Amfiteatrov (1862–1938), who lived in exile in Italy during those years. The impetus for the correspondence and its key topic was Bryusov’s report “Incinerated” at the ceremonial meeting of the Society of Lovers of Russian Literature on April 27, 1909 in Moscow, which was dedicated to the centenary anniversary of N.V. Gogol. Bryusov’s speech caused heated controversy in the press, and Amfiteatrov spoke out in print to support the poet. Along the way, the topics of the epistolary dialogue became articles by contemporaries about Gogol. Part of the correspondence is devoted to a discussion of Bryusov’s books, primarily his novel The Altar of Victory, as well as the collections Earth’s Axis and Mirror of Shadows. The correspondence contains interesting and sometimes unexpected assessments of contemporary writers. The article provides the published texts with detailed historical and literary comments.